ANALISIS PENGARUH KEMUDAHAN PEMAKAIAN SITUS, MUTU INFORMASI, KEPERCAYAAN PEMBELIAN, DAN KESAN HARGA TERHADAP NIAT BELANJA DARING DI OLX.CO.ID PADA MAHASISWA UNIVERSITAS DIPONEGORO SEMARANG - Endigalani, Annisa; Dirgantara, I Made Bayu (Diponegoro Journal of Management, 2017)
This research aims to analyze the influence of ease of use site, quality information, purchasing trust, and the impression of price against visitor’s shopping intention on OLX.co.id.The sampling method used on this research is probability sampling with random sampling technique. Samples were collected from 258 respondents who are students of Diponegoro University Semarang who have visited the site OLX.co.id. Analysis method used here is multiple regression analysis which includes validity test, reliability test, classic assumption test, multiple linear regression test, t-test, f-test, determination testThe result showed that the ease of use of the site, quality informartion, purchasing trust, and the impression of price has positive influence towards the shopping intention.